STRATEGI PENGEMBANGAN KAMPUNG WISATA ROTAN GALMANTRO YANG BERKELANJUTAN - Ivien Aryo Puspita Wardani; R. Siti Rukayah; Agung Dwiyanto (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2024)
Abstract: Galmantro Rattan Tourism Village has attractions such as rattan handicrafts, rattan production houses with traditional and modern architecture, friendly residents and easy access from the city center. Tourism activities with the craft industry becoming a tourist village can create job opportunities, reduce proverty levels and encourage economic development. Galmantro Rattan Tourism Village has potential to develop into a sustainable tourism village. The development of sustainable tourism village is a form of environmental, nature, culture and welfare of the local community. This study intended to provide a strategy formulation about sustainable development of Galmantro Rattan Tourism Village. The method used in this study is mixed method that combines quantitative and qualitative. Strategy formulation will be analyzed using SWOT analysis. There are four strategies, namely optimizing the management of tangible and intangible cultural tourism, utilizing open space as a tourist attraction facility, optimize the potential of home-based enterprises by processing waste and using efficient energy as well as improving accessibility and transportation system.Abstrak: Kampung Wisata Rotan Galmantro memiliki daya tarik seperti kerajinan rotan, rumah produksi kerajinan rotan dengan arsitektur tradisional dan modern, keramahan warga dan mudah dijangkau dari pusat kota. Kegiatan pariwisata dengan industri kerajinan menjadi kampung wisata dapat menciptakan peluang kerja, menurunkan tingkat kemiskinan dan mendorong pengembangan ekonomi. Kampung Wisata Rotan Galmantro berpotensi untuk berkembang menjadi kampung wisata yang berkelanjutan. Pengembangan kampung wisata berkelanjutan merupakan bentuk kepedulian terhadap lingkungan, alam, budaya dan kesejahteraan masyarakat setempat. Tujuan dari penelitian ini untuk memberikan perumusan strategi mengenai pengembangan kampung wisata rotan Galmantro yang berkelanjutan. Metode penelitian yang digunakan adalah mix method yang menggabungan teknik kuantitatif dan kualitatif. Perumusan strategi akan di analisis menggunakan analisis SWOT. Penelitian ini menghasilkan empat strategi yaitu mengoptimalkan pengelolaan wisata budaya tangible dan intangible, pemanfataan ruang terbuka sebagai fasilitas atraksi wisata, mengoptimalkan potensi HBE dengan pengolahan limbah dan penggunaan energi yang efisien serta meningkatkan kemudahan aksesibilitas dan sistem transportasi.